Diverging socioeconomic inequality in life expectancy of Francophones and Anglophones in Montréal, Québec: Tobacco to blame? - Auger, Nathalie; Harper, Sam; Barry, Amadou D. (Journal of Public Health: From Theory to Practice, 2013)
Aim We evaluated the ages and causes of death contributing to life expectancy gaps between economically advantaged and disadvantaged Francophones and Anglophones of Montréal, a Canadian metropolitan centre. Subject and Methods We partitioned the life expectancy gap at birth between socioeconomically disadvantaged and advantaged Francophones and Anglophones of Montréal (Québec) into age and cause of death components for two periods (1989–1993, 2002–2006). Changes in the contributions of causes over time were evaluated. Results Life expectancy was lower for disadvantaged Francophones and Anglophones by 5 years in men and 1.6 years in women compared with advantaged individuals. Over time, the socioeconomic gap widened for Francophones (men 0.3 years, women 2.8 years), due to smaller reductions in mortality from tobacco-related causes (cardiovascular, cancer, respiratory) in disadvantaged than in advantaged Francophones, especially after age ≥65 years (except lung cancer mortality that increased, particularly in disadvantaged women). The socioeconomic gap narrowed, however, for Anglophones (men 1.0 year, women 0.6 years), due to greater reductions in cardiovascular mortality in disadvantaged than advantaged Anglophones. Conclusion Socioeconomic inequalities in life expectancy decreased for Anglophones but increased for Francophones in Montréal due to underlying trends in tobacco-related mortality. Despite strong tobacco control laws in Canada, socioeconomic inequality in tobacco-related mortality is widening for Francophones in Montréal.

Life expectancy gap between the Francophone majority and Anglophone minority of a Canadian population - Auger, Nathalie; Harper, Sam; Barry, Amadou D.; Trempe, Normand; Daniel, Mark (European Journal of Epidemiology, 2012)
Language is an important determinant of health, but analyses of linguistic inequalities in mortality are scant, especially for Canadian linguistic groups with European roots. We evaluated the life expectancy gap between the Francophone majority and Anglophone minority of Québec, Canada, both over time and across major provincial areas. Arriaga’s method was used to estimate the age and cause of death groups contributing to changes in the life expectancy gap at birth between 1989–1993 and 2002–2006, and to evaluate patterns across major provincial areas (metropolitan Montréal, other metropolitan centres, and small cities/rural areas). Life expectancy at birth was greater for Anglophones, but the gap decreased over time by 1.3 years (52% decline) in men and 0.9 years (47% decline) in women, due to relatively sharper reductions in Francophone mortality from several causes, except lung cancer which countered reductions in women. The life expectancy gap in 2002–2006 was widest in other metropolitan centres (men 5.1 years, women 3.2 years), narrowest in small cities/rural areas (men 0.8 years, women 0.7 years), and tobacco-related causes were the main contributors. Only young Anglophones <40 years in small cities/rural areas had mortality higher than Francophones, resulting in a narrower gap in these areas. Differentials in life expectancy favouring Anglophones decreased over time, but varied across areas of Québec. Tobacco-related causes accounted for the majority of the current life expectancy gap.

Contribution of local area deprivation to cultural-linguistic inequalities in foetal growth restriction: Trends over time in a Canadian metropolitan centre - Auger, Nathalie; Park, Alison L.; Daniel, Mark (Health & Place, 2013)
This study investigated temporal trends in heterogeneity of foetal growth restriction across neighbourhood deprivation levels for two culturally distinct communities (Anglophones and Francophones) in a North American metropolitan centre. Inequalities in foetal growth restriction related to deprivation fell from 1989 to 2008 for Francophones, but initial improvements for Anglophones later reversed with a rise in poor foetal growth in the most materially disadvantaged and, unexpectedly, advantaged areas as well. Inequalities in foetal growth restriction related to neighbourhood material deprivation may be emerging in this minority Anglophone population. Potential mechanisms underlying these trends are discussed, as well as implications for perinatal health policy.

Francophone and Anglophone perinatal health: Temporal and regional inequalities in a Canadian setting, 1981-2008 - Auger, Nathalie; Park, Alison L.; Harper, Sam (Francophone and Anglophone perinatal health: Temporal and regional inequalities in a Canadian setting, 2012)
Objectives We evaluated temporal and regional inequalities in adverse birth outcomes between Anglophones and Francophones of a Canadian province. Methods Odds ratios and rate differences in preterm birth (PTB, <37 gestational weeks) and small-for-gestational-age (SGA) birth were computed for Anglophones relative to Francophones for singleton live births in Québec from 1981 to 2008 (N = 2,292,237), adjusting for maternal characteristics. Trends over time and residential region were evaluated. Results Rates of PTB and SGA birth overall were lower for Anglophones relative to Francophones, but temporal and regional trends varied by outcome. Although PTB rates increased over time, inequalities between Francophones and Anglophones were relatively stable. In contrast, inequalities in SGA birth narrowed over time as Francophone rates declined more than Anglophones. Inequalities in SGA birth favored Anglophones overall, but the gap gradually reversed in Montréal (the largest metropolitan center) to currently favor Francophones. Conclusions PTB and SGA birth rates favored Anglophones over Francophones. The linguistic gap was generally stable over time for PTB, but narrowed or reversed for SGA birth. Language may be used to capture inequalities in perinatal health in countries where different linguistic groups predominate.

Santé mentale des jeunes des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : l’état des lieux - Beaton, Ann M.; Benoit, Monique; Mulatris, Paulin; Dupuis, Jérémie B. (/Youth Mental Health in Official Language Minority Communities (OLMCs) in Canada: Situation Analysis Minorités linguistiques et société, 2018)

My health, your health, our health at Bishop's University [infographic] - Bishop's University; Consortium National de formation en Santé; Université de Saint-Boniface (2019)

Santé mentale et maladies mentales des jeunes francophones de 15 à 24 ans : données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale 2012 - Bouchard, Louise; Batista, Ricardo; Colman, Ian (Minorités linguistiques et société, 2018)
a plupart des maladies mentales apparaissent à l’adolescence ou au début de la vie adulte ; elles influent sur les réussites scolaires, les possibilités et les succès professionnels ainsi que les relations personnelles et peuvent avoir des répercussions tout au long de la vie. Bien que la majorité des jeunes traversent leur adolescence sans problèmes, une proportion suffisamment importante montre toutefois un profil préoccupant dont il faut prendre acte. L’objectif de cet article est de brosser, à partir des données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale (ESCC-SM 2012), un portrait de la santé mentale des jeunes francophones de 15 à 24 ans vivant en situation linguistique minoritaire et de le comparer à celui des jeunes francophones vivant au Québec. Mots-clés : identité ethnolinguistique, continuité culturelle, minorité francophone, jeunes adultes, santé mentale

Minorités de langue officielle du Canada : égales devant la santé ? - Bouchard, Louise; Desmeules, Martin (Presses de l’Université du Québec, 2011)

La santé mentale des francophones et des anglophones vivant en situation minoritaire au Canada [infographie] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Mental health status of Francophones and Anglophones living in minority situations in Canada [infographic] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Profil santé mentale des communautés francophones en situation minoritaire au Canada. Rapport abrégé - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa; Colman, Ian (Université d'Ottawa et Institut du Savoir Montfort, 2019)

Health profile of English-speaking minority communities in Canada [infographic] - Bouchard, Louise; Sampasa-Kanyinga, Hugues; Mukaneza, Anne (2018)
fs-ref-orig: Bouchard, L., Sampasa-Kanyinga, H., & Mukaneza, A. (2018). Health profile of English-speaking minority communities in Quebec [infographic]. University of Ottawa and Institut du savoir Montfort. fs-code-orig: Bouchard-2018f

Profil santé des communautés anglophones en situation minoritaire au Québec [infographie] - Bouchard, Louise; Sampasa-Kanyinga, hugues; Mukaneza, anne (2018)
fs-ref-orig: Bouchard, L., Sampasa-Kanyinga, H. et Mukaneza, A. (2018). Profil santé des communautés anglophones en situation minoritaire au Québec [infographie]. Université d’Ottawa et Institut du savoir Montfort. fs-code-orig: Bouchard-2018e

Suicide mortality gap between Francophones and Anglophones of Quebec, Canada - Burrows, Stephanie; Auger, Nathalie; Tamambang, Lum; Barry, Amadou. D. (Social psychiatry and psychiatric epidemiology, 2013)
Purpose Few studies evaluate language-group differences in suicide mortality. This study assessed the suicide mortality gap between Francophones and Anglophones of Quebec, Canada according to age, sex, method, region and socioeconomic deprivation. Methods Suicide decedents were extracted from the Quebec death file for 1989–2007 (N = 24,465). Age- and sex-specific suicide mortality rates were calculated for four periods (1989–1993, 1994–1998, 1999–2003, 2004–2007) for Francophones and Anglophones aged ≥10 years. Age-standardized rates of suicide by method, region, and level of social and material deprivation were calculated for each sex. Rate ratios and rate differences were estimated. Results Suicide rates for Francophones were two to three times higher than rates for Anglophones, and differences were greatest for adults aged 25–64 years. Francophone males had more than two times the rate of suicide by hanging or firearms than Anglophone males. Francophone females had twice the rate of hanging, poisoning or firearm suicide as Anglophone females, although precision was low. Francophone-Anglophone suicide mortality gaps were higher in urban areas despite lower suicide rates, and varied little across levels of social and material deprivation. Conclusions There was a large suicide mortality gap between Francophones and Anglophones of Quebec; especially, among adults aged 25–64 years.

Availability, accessibility and acceptability of english-language mental health services for the Estrie region’s english-speaking population: Service user and provider perspectives - Charpentier, Claude; Stout, Dale; Benoit, Annie; Poulin, Edith; Philip, Christopher (Journal of Eastern Townships Studies, 2011)
Mental illness affects about 1 in 5 Canadians during their lifetime but only approximately 30% of people needing help actually access mental health ser vices (Gravel, Connolly & Bédard, 2004). This low access rate is worrisome and may not accurately depict the reality as it is lived out by linguistic minorities. The present study documents both the need for and access to English-lan guage mental health services by the Estrie region’s English-speaking minority. Intending to record their needs and access experiences against the backdrop of available English-language mental health services, both users and providers of these services were surveyed in tandem. This novel approach to mental health needs assessment research shows the precarious situation of this minority community (high need/low access to language-congruent mental health ser vices) to be further compromised by misperceptions of service availability.

Ma santé, ta santé, notre santé. Étude sur la santé mentale et les comportements à risque des jeunes adultes dans cinq universités au coeur du Canada - de Moissac, Danielle; Gueye, Ndeye Rokhaya; Rocque, Rhéa (Consortium national de formation en santé, Université de Saint-Boniface, 2019)
La transition de l’adolescence à la vie adulte constitue une des plus importantes transitions de la vie. À ce stade, le jeune doit développer des habiletés pour être en mesure de se prendre en charge et gérer ses responsabilités académiques et financières tout en maintenant un mode de vie sain. Des études démontrent que des perturbations à ce stade de vie peuvent avoir des conséquences importantes sur la santé psychologique et l’adaptation au changement, et qu’une instabilité émotionnelle peut avoir des retombées sur la performance et le fonctionnement psychosocial. Le milieu universitaire occupe une place privilégiée en tant que lieu d’intervention pour la promotion de la santé pour ces jeunes en raison du contact direct avec les étudiants au cours de plusieurs années. Une stratégie en matière de santé mentale, développée par la Commission de la santé mentale du Canada, souligne que les efforts de promotion en santé mentale et de prévention des troubles mentaux seront plus efficaces si les axes suivants sont respectés 1) savoir à qui s’adresser; 2) renforcer les éléments de protection et réduire les facteurs de risque; 3) fixer des buts clairs; 4) donner aux collectivités ce dont elles ont besoin pour agir; et 5) planifier pour le long terme. Ce projet de recherche s’inspire de cette stratégie : notre but à long terme est de favoriser le bien-être des jeunes adultes qui fréquentent un établissement universitaire en développant un outil de dépistage et des initiatives d’appui soutenables sur le campus et dans la communauté, selon les ressources disponibles. Pour ce faire, nous devons d’abord prendre connaissance de l’état de santé mentale de la population étudiante et des facteurs de risques et de protection qui leur sont propres. Ainsi, les efforts de prévention seront plus efficaces puisqu’ils seront conçus en fonction des besoins de la population cible et en consultation avec cette dernière. Cette étude a été menée dans cinq universités dans trois provinces, soit le Manitoba, l’Ontario et le Québec, dans le but de mieux comprendre l’effet du contexte linguistique sur la santé mentale et les comportements à risque des jeunes universitaires. Les cinq établissements choisis sont principalement des petites universités en contexte linguistique majoritaire (Brandon University et Université du Québec en Abitibi-Témiscamingue) ou minoritaire (Université de Saint-Boniface et Université Bishop’s). De plus, des participants de l’unique université bilingue du pays (Université d’Ottawa) ont participé. Ainsi, nous serons en mesure d’analyser les données en fonction de divers facteurs déterminants, dont le milieu linguistique dans lequel évolue l’étudiant. L’objectif principal de l’étude est de prendre connaissance de l’état de santé mentale et des comportements à risque prédominants des jeunes universitaires en contextes linguistiques majoritaires et minoritaires au Canada et d’identifier les facteurs de protection et de risque associés à leur bien-être. Notre but ultime est d’appuyer les étudiants, particulièrement ceux dans le besoin, dans leur atteinte d’une réussite académique. Ce rapport est descriptif : il présente les données générales se rapportant aux profils sociodémographique et ethnolinguistique, à l’état de santé mentale et aux comportements associés à cet état, ainsi qu’à la sécurité routière, au taxage et au harcèlement sexuel, aux pratiques sexuelles, à la consommation d’alcool, de drogues et de tabac, et à l’usage des nouvelles technologies; le tout, selon le genre et pour chacun des établissements d’enseignement postsecondaire. Un sondage a été distribué, sur papier ou en ligne, en fin novembre 2018 et en février 2019; au total, 2075 étudiants ont participé. Des analyses statistiques de fréquences et de proportions, selon le genre, ont été utilisées pour décrire les participants et leurs comportements.
fs-ref-orig: de Moissac, D., Gueye, N. R. et Rocque, R. (2019). Ma santé, ta santé, notre santé. Étude sur la santé mentale et les comportements à risque des jeunes adultes dans cinq universités au coeur du Canada. Consortium national de formation en santé, Université de Saint-Boniface et Université du Québec en Abitibi-Témiscamingue. fs-code-orig: de Moissac-2019b

My Health, your health, our health. A study on mental health and risk-taking behaviors of young adults on five university campuses in the heart of Canada - de Moissac, Danielle; Gueye, Ndeye Rokhaya; Rocque, Rhéa (Consortium national de formation en santé, Université de Saint-Boniface, 2019)
The transition from adolescence to adulthood is a time of dramatic change in one’s life. At this stage, youth are developing skills to be able to support themselves and manage academic and financial responsibilities, while maintaining a healthy lifestyle. Studies have shown that disturbances at this stage may have a strong impact on one’s psychological health and ability to adapt to change; emotional instability may have repercussions on performance and psychosocial functioning. Due to direct contact with young adults, postsecondary institutions are priviledged settings for health promotion activities. A mental health strategy developed by the Mental Health Commission of Canada suggests that to successfully promote health, and treat and prevent mental health issues, the following should be considered: 1) know who to reach; 2) strengthen protective factors and reduce risk factors; 3) set clear goals; 4) give communities what they need to take action; and 5) plan for the long term. This research project builds on this strategy. Our long term goal is to promote the well-being of university students by developing a screening tool and developing sustainable initiatives on campus and within the community, taking into consideration available resources. As such, we must first gain insight into the mental health status of the student population, including the risk and protective factors specific to these students. Thus, health promotion efforts will be more efficient, as they will have been created according to student needs and in consultation with this population. This study was conducted in five universities in three provinces, Manitoba, Ontario and Quebec, to gain insight into the impact of the linguistic context on mental health and risk-taking behaviors of students. The five participating universities were chosen mainly because of their small size and linguistic environment: Brandon University and the Université du Québec en Abitibi-Témiscamingue are in linguistic majority settings, whereas the Université de Saint-Boniface and Bishop’s University are in linguistic minority communities. In addition, participants were recruited from the only bilingual university in the country (University of Ottawa). Thus, data will be analysed according to various influencing factors, including the linguistic environment. The main objective of this study is to gain insight into the mental health status and predominant risk behaviors of university students in both majority and minority linguistic settings in Canada and to identify protective and risk factors relative to their well-being. The ultimate goal is to help those in need achieve academic success. This report is descriptive: it presents general data related to sociodemographic and ethnolinguistic profiles, mental health and related behaviors, road safety, bullying and sexual harassment, sexual practices, alcohol, drug and tobacco use and use of new technologies, according to gender, for each of the postsecondary institutions. A survey was conducted online or in print form at the end of November 2018 and in February 2019. In total, 2075 students participated. Statistical analysis of frequencies and proportions according to gender were used to describe participants and their behaviors
fs-ref-orig: de Moissac, D., Gueye, N. R., & Rocque, R. (2019). My Health, your health, our health. A study on mental health and risk-taking behaviors of young adults on five university campuses in the heart of Canada. Consortium national de formation en santé, Université de Saint-Boniface et Université du Québec en Abitibi-Témiscamingue. fs-code-orig: de Moissac-2019c

Les disparités d'accès aux soins de santé parmi la minorité de langue officielle au Québec - Falconer, James; Quesnel-Vallée, Amélie (Recherches sociographiques, 2014)
Cette étude examine l’effet de l’aptitude en français sur la santé et sur les besoins de soins de santé non satisfaits au Québec, en utilisant un modèle multiple de régression logistique. Nos résultats indiquent que les anglophones unilingues du Québec sont 26 % plus susceptibles que les anglophones bilingues à se déclarer en mauvaise santé. Théoriquement, ce mauvais état de santé devrait mener à une utilisation accrue des soins de santé. Cependant, malgré leur mauvais état de santé, les anglophones unilingues sont 52 % plus susceptibles de déclarer des besoins en soins de santé non satisfaits. Ces disparités dans l’état de santé ainsi que dans l’accès aux soins de santé s’expliquent par l’aptitude à s’exprimer en français. Par ailleurs, ces effets ne sont pas modifiés par l’inclusion de variables potentiellement confondantes telles que les caractéristiques sociodémographiques et socioéconomiques. Les résultats suggèrent que ce sont les politiques visant à réduire les obstacles à l’accès aux soins de santé des populations minoritaires qui pourraient améliorer l’accès aux soins, et, éventuellement, la santé des anglophones unilingues du Québec. Mots-clés : populations minoritaires de langue officielle, anglophones, Québec, utilisation des services de santé, inégalités de santé, accès aux soins de santé

Prévalence de la dépression majeure chez les arthritiques des populations canadiennes : étude comparative entre anglophones majoritaires et francophones en situation linguistique minoritaire - Fotsing, Salomon; Nzokem, Aubain H.; Grenier, Jean; Imbeault, Pascal; Batal, Malek; Bouchard, Louise; Chomienne, Marie-Hélène (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif La santé mentale et l’arthrite sont deux maladies reconnues comme étant des enjeux majeurs en santé publique. La situation minoritaire des francophones est reconnue comme un déterminant de la santé. L’objectif de cette étude est de déterminer la prévalence de la dépression majeure chez les arthritiques adultes des populations francophones minoritaires comparativement à la majorité anglophone. Méthode Analyse secondaire de l’ESCC (fusion de 2003 (cycle 2.1), 2005 (cycle 3.1), 2007 (cycle 4.1), 2008 et 2009) excluant le Québec. La variable langue a été construite selon un algorithme pré-existant réunissant la langue maternelle, de conversation, d’entrevue et de préférence. La dépression majeure était définie selon les critères du DSM IV. La présence ou non d’arthrite était une variable auto-rapportée. Les prévalences et rapports de cotes pour la dépression dans la population arthritique ont été calculés et ajustés en fonction de divers facteurs (socioéconomiques, isolement social, accès aux services de santé). Résultats L’étude identifiait 159 426 anglophones et 10 658 francophones. Parmi les sujets avec arthrite (27 %), la prévalence de la dépression était de 8,5 % et de 8,4 % chez les francophones et les anglophones, respectivement; chez les hommes, les anglophones étaient plus à risque de faire une dépression que les francophones: OR=2,36 (IC 95%: 2,07-2,70) c. OR=1,87 (IC 95%: 1,20-2,91). Cette tendance ne se retrouvait pas chez les femmes. Conclusion Notre échantillon démontre que dans une population arthritique, la dépression semble toucher plus particulièrement les hommes anglophones. Cependant il faut souligner la petite taille de l’échantillon.

Physical inactivity among Francophones and Anglophones in Canada - Imbeault, Pascal; Makvandi, Ewa; Batal, Malek; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective Leisure-time physical activity participation is influenced by various socio-demographic factors. Recent evidence suggests that being part of a minority negatively impacts an individual’s health status. The objective of this study was to compare inactive leisure-time physical activity between the Francophone minority and the Anglophone majority in Canada. Methods Data from the fusion of cycles 2.1, 3.1, 4.1, 2008 and 2009 of the Canadian Community Health Survey (CCHS) were used. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. Leisure-time physical activity was based on a questionnaire provided during the interview. Factors associated with inactive leisure time were examined using logistic regression models. Results Francophones were more likely than Anglophones to be physically inactive in their leisure time (49.1% vs. 47.2%). A greater percentage of Francophones had poor self-perceived health, were older, were single, had lower education, had higher rate of unemployment and lived in rural areas compared to Anglophones. When these socio-demographic factors were taken into account, there were no further differences in the likelihood of being inactive between Francophones and Anglophones. Conclusion The Francophone minority in Canada is characterized by socio-demographic factors that have a negative impact on leisure-time physical activity participation.

Do you speak English? Traitement sociopolitique de l’accessibilité aux services en santé mentale pour les anglophones du Québec - Kirouac, Laurie; Perreault, Isabelle (Minorités linguistiques et société, 2018)
À la fin des années 1970, le Québec se dote de la Charte de la langue française (Loi 101), qui modifie l’encadrement de la question de la langue de prestation des services de santé et de services sociaux. Parallèlement, de nombreux rapports, comités d’étude et politiques modifient en profondeur les pratiques institutionnelles et communautaires à l’endroit des personnes aux prises avec des problèmes de santé mentale. Depuis ce contexte de grandes transformations, où certaines réponses politiques ont été apportées aux préoccupations linguistiques, qu’en est-il de l’accès aux soins de santé mentale pour les anglophones du Québec ? Nous proposons de retracer dans ses grandes lignes l’évolution du traitement sociopolitique qui a été fait de la question de l’accessibilité des services en santé mentale pour les personnes anglophones en accordant une attention particulière à la situation montréalaise. Mots-clés : Québec, anglophones, santé mentale, minorité linguistique, services de santé

La santé des populations de langue officielle en situation minoritaire [numéro thématique] - Leis, Anne; Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Cette page éditoriale présente un numéro spécial de la Revue canadienne de santé publique qui comporte 16 articles compilant certains résultats de recherches obtenus par des chercheurs affiliés au RISF, au RRASFO et à l’Institut de recherche de l’Hôpital Montfort (IRHM), ainsi qu'un commentaire exposant les enjeux d'accès aux services de santé linguistiquement concordant au Pays de Galles.
fs-ref-orig: Leis, A. et Bouchard,

Identité, culture et représentations de la santé et des maladies - Lévesque, Annabel (Cahiers franco-canadiens de l’Ouest, 2015)
La santé et les maladies représentent des concepts subjectifs qui varient en fonction de nombreux facteurs, notamment la culture d’appartenance. Étant donné le contexte multiculturel canadien, il importe de considérer le contact interculturel lorsqu’on s’interroge au sujet des représentations de la santé et des maladies chez les groupes minoritaires puisque ces derniers sont soumis à l’influence d’autres cultures, dont la culture du groupe dominant. Ainsi, le degré d’identification à la culture d’origine et à la culture dominante détermine les représentations auxquelles souscrivent les individus issus d’un groupe minoritaire. Chez ceux qui s’identifient à leur culture d’origine, on note un lien entre leur état de santé et la vitalité culturelle et linguistique de leur communauté. Les efforts visant à promouvoir la santé et le bien-être de ces individus devraient donc être axés sur le maintien de leur héritage culturel et linguistique. Les professionnels de la santé, pour leur part, devraient engager le dialogue avec leurs patients au sujet de leurs représentations culturelles de la santé et des maladies, et ce, dans un climat empreint de respect. Cette pratique pourrait contribuer à la satisfaction des patients avec les soins reçus et, par le fait même, à l’adoption de comportements sains.

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Official language minority communities in Canada: Is linguistic minority status a determinant of mental health? - Puchala, Chassidy; Leis, Anne; Lim, Hyun; Tempier, Raymond (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
fs-ref-orig: Puchala, C., Leis, A., Lim, H., & Tempier, R. (2013). Official language minority communities in Canada: Is linguistic minority status a determinant of mental health? Canadian Journal of Public Health, 104(1), 5‑11. https://www.ncbi.nlm.nih.gov/pmc/Articles/PMC6973939/pdf/41997_2013_Article_1040605.pdf fs-code-orig: Puchala-2013

Accès interrégional aux services sociaux et de santé pour les personnes d’expression anglaise de l’est de Québec - Richardson, Mary; Gagnon, Hélène (Committee for Anglophone Social Action et Partenaires communautaires Jeffery Hale, 2015)
Cette étude visait à mieux comprendre ce que vivent les anglophones des régions de l‘est du Québec qui doivent se déplacer vers des centres urbains pour recevoir des services de santé spécialisés.

Favoriser le rétablissement dans sa langue. Orientation en santé mentale en français. Version révisée - Société Santé en français (Version révisée, 2014)
fs-ref-orig: Société santé en français. (2012). Favoriser le rétablissement dans sa langue. Orientation en santé mentale en français. Version révisée. fs-code-orig: Société Santé en français-2014

Comparing mental health of Francophone populations in Canada, France, and Belgium: 12-month prevalence rates of common mental disorders (part 1) - Tempier, Raymond; Vasiliadis, Helen-Maria; Gilbert, Fabien; Demyttenaere, Koen; Bruffaerts, Ronny; Bonnewyn, Anke; Lépine, Jean-Pierre; Gasquet, Isabelle; Mosier, Karen; Lesage, Alain; Puchala, Chassidy; Lepnurm, Marje; et al. (The Canadian Journal of Psychiatry, 2010)
Objective: To compare the 12-month prevalence of common mental disorders among francophones in Canada, France, and Belgium. This is the first article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: This is a secondary analysis of data from the Canadian Community Health Survey: Mental Health and Well-Being (CCHS 1.2) in 2002 and the European Study of Epidemiology of Mental Disorders-Mental Health Disability (ESEMeD) from 2001 to 2003, where comparable questionnaires were administered to representative samples of adults in Canada, France, and Belgium. In Canada, francophone respondents living in Quebec (n = 7571) and outside Quebec (n = 500) completed the French version of the CCHS 1.2 questionnaire. Francophone respondents in Belgium (n = 389) and in France (n = 1436) completed the French version of the ESEMeD population survey questionnaire. Major depressive episodes (MDEs), specific anxiety disorders (ADs), and alcohol abuse and (or) dependence disorders' rates were assessed. Results: The overall prevalence rate for the presence of any MDE, AD, or alcohol abuse and (or) dependence was similar in all francophone populations studied in Canada and Europe and averaged 8.5%. Conclusions: Mental disorders were equally distributed in all francophone populations studied. Cross-national comparisons continue to be instrumental in providing information useful for the creation of appropriate policies and programs for specific subsets of populations.

Comparing mental health of Francophones in Canada, France, and Belgium: 12-month and lifetime rates of mental health service use (part 2) - Tempier, Raymond; Vasiliadis, Helen-Maria; Gilbert, Fabien; Demyttenaere, Koen; Bruffaerts, Ronny; Lépine, Jean-Pierre; Gasquet, Isabelle; Lepnurm, Marje; Lesage, Alain; Puchala, Chassidy; Mosier, Karen; Kovess-Masféty, Viviane (The Canadian Journal of Psychiatry, 2010)
Objectives: To compare 12-month and lifetime service use for common mental disorders in 4 francophone subsamples using data from national mental health surveys in Canada, Quebec, France, and Belgium. This is the second article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: Comparable World Mental Health-Composite International Diagnostic Interviews (WMH-CIDI) were administered to representative samples of adults (aged 18 years and older) in Canada during 2002 and in France and Belgium from 2001 to 2003. Two groups of francophone adults in Canada, in Quebec (n = 7571) and outside Quebec (n = 500), and respondents in Belgium (n = 389) and France (n = 1436) completed the French version of the population survey. Prevalence rates of common mental health service use were examined for major depressive episodes and specific anxiety disorders (that is, agoraphobia, social phobia, and panic disorder). Results: Overall, most francophones with mental disorders do not seek treatment. Canadians consulted more mental health professionals than their European counterparts, with the exception of psychiatrists. Conclusions: Patterns of service use are similar among francophone populations. Variations that exist may be accounted for by differences in health care resources, health care systems, and health insurance coverage.

Désinstitutionalisation psychiatrique en Acadie, en Ontario francophone et au Québec, 1930-2013 - Thifault, Marie-Claude; Dorvil, Henri (Presses de l’Université du Québec, 2015)

Regards croisés Ontario-Québec : les services de soins de santé mentale des communautés de langue officielle en situation minoritaire de 1950 à nos jours - Thifault, Marie-Claude; Lebel, Marie; Perreault, Isabelle; Desmeules, Martin (Reflets, 2012)
Considérant qu’un Canadien sur neuf hospitalisé pour maladie mentale retournera à l’urgence moins d’un mois après sa sortie d’hôpital, il importe de documenter, dans une perspective socio-historique, les itinéraires « transinstitutionnels » des personnes souffrant de troubles psychiques. Nous proposons ici une note de recherche sur l’enquête que nous menons sur l’évolution des services de soins de santé mentale des communautés de langue officielle en situation minoritaire, en particulier, les communautés francophones de l’Est et du Nord ontarien ainsi que de la communauté anglophone de l’Ouest du Québec. Ces regards croisés entre deux régions francophones de l’Ontario et le Montréal anglophone visent une meilleure compréhension de l’impact des facteurs de « langue de service » et de « culture » sur la santé mentale des communautés francophones en situation minoritaire (CFSM). Mots-clés : services de santé mentale, désinstitutionnalisation, minorités linguistiques, Ontario, Québec

Avoidable mortality of the two main linguistic communities in Québec. Language as a determinant of health status and service quality - Trempe, Normand; Diogo Barry, Amadou D.; Lussier, Marie-Hélène.; Lo, Ernest (Institut national de santé publique du Québec, 2013)
fs-ref-orig: Trempe, N., Diogo Barry, A., Lussier, M.-H., & Lo, E. (2013). Avoidable mortality of the two main linguistic communities in Québec. Language as a determinant of health status and service quality. Institut national de santé publique du Québec. fs-code-orig: Trempe-2013b

La mortalité évitable des deux principales communautés linguistiques du Québec. La langue, déterminant de l'état de santé et la qualité des services - Trempe, Normand; Diogo Barry, Amadou; Lussier, Marie-Hélène; Lo, Ernest (Institut national de santé publique du Québec, 2013)
fs-ref-orig: Trempe, N., Diogo Barry, A., Lussier, M.-H. et Lo, E. (2013). La mortalité évitable des deux principales communautés linguistiques du Québec. La langue, déterminant de l'état de santé et la qualité des services. Institut national de santé publique du Québec. fs-code-orig: Trempe-2013a

Portrait de la prématurité et des naissances ayant un faible poids pour l’âge gestationnel dans les communautés linguistiques au Québec, 1989 à 2010 - Tu, Mai Thanh; Bilodeau-Bertrand, M.; Auger, Marianne (Institut national de santé publique du Québec, 2018)
fs-ref-orig: Tu, M. T., Bilodeau-Bertrand, M. et Auger, N. (2018). Portrait de la prématurité et des naissances ayant un faible poids pour l’âge gestationnel dans les communautés linguistiques au Québec, 1989 à 2010. Institut national de santé publique du Québec. fs-code-orig: Tu-2018c

Portrait of preterm and small-for-gestational-age births by linguistic community in Québec, 1989 to 2010 - Tu, Mai Thanh; Bilodeau-Bertrand, Marianne; Auger, Nathalie (Institut national de santé publique du Québec, 2018)
fs-ref-orig: Tu, M. T., Bilodeau-Bertrand, M., & Auger, N. (2018). Portrait of preterm and small-for-gestational-age births by linguistic community in Québec, 1989 to 2010. Institut national de santé publique du Québec. fs-code-orig: Tu-2018d

Health profile of linguistic communities in Québec - Tu, Mai. Thanh; Lussier, Marie-Hélène.; Martel, Sylvie; Blaser, Christine (Institut national de santé publique du Québec, 2018)
fs-ref-orig: Tu, M. T., Lussier, M.-H., Martel, S., & Blaser, C. (2018). Health profile of linguistic communities in Québec. Institut national de santé publique du Québec. fs-code-orig: Tu-2018b

Portrait de santé des communautés linguistiques du Québec - Tu, Mai Thanh; Lussier, Marie-Hélène; Martel, Sylvie; Blaser, Christine (Institut national de santé publique du Québec, 2018)
fs-ref-orig: Tu, M. T., Lussier, M.-H., Martel, S. et Blaser, C. (2018). Portrait de santé des communautés linguistiques du Québec. Institut national de santé publique du Québec. fs-code-orig: Tu-2018a

Enjeux des services sociaux et de santé en contexte bilingue ou multilingue national. Revue de littérature - van Kemenade, Solange; Forest, Mariève (Secrétariat national du Consortium national de formation en santé, 2015)